Transection of the origin of the innominate artery: A rare sequela of blunt traumatic chest trauma. (June 2020) - Lovelock, T.; Cheng, A.; Negri, J.; Fitzgerald, M.
Abstract: Blunt traumatic transection of the innominate artery is rare. We describe a case of a 36-year-old male who presented to our Emergency & Trauma Center after being struck by a motor vehicle at high speed. Computerised Tomography (CT) scanning after the patient was stabilised facilitated the prompt diagnosis of the injury. The patient underwent open repair by midline sternotomy, with debranching of the innominate artery, using hypothermic circulatory arrest as a neuroprotective measure. The patient was successfully extubated on post-operative day 3, without neurological deficit. We provide our experience as an option for treating any patient that presents with such an injury.